Understanding CAR T cell therapy and its role in ovarian cancer and peritoneal carcinomatosis from ovarian cancer - Domínguez-Prieto, Víctor; Qian, Siyuan; Villarejo-Campos, Pedro; Meliga, Cecilia; González-Soares, Sara; Guijo Castellano, Ismael; Jiménez-Galanes, Santos; García-Arranz, Mariano; Guadalajara, Héctor; García-Olmo, Damián (Frontiers in Oncology, 2023)
Ovarian cancer is the seventh most common cancer worldwide in women and the most lethal gynecologic malignancy due to the lack of accurate screening tools for early detection and late symptom onset. The absence of early-onset symptoms often delays diagnosis until the disease has progressed to advanced stages, frequently when there is peritoneal involvement. Although ovarian cancer is a heterogeneous malignancy with different histopathologic types, treatment for advanced tumors is usually based on chemotherapy and cytoreduction surgery. CAR T cells have shown promise for the treatment of hematological malignancies, though their role in treating solid tumors remains unclear. Outcomes are less favorable owing to the low capacity of CAR T cells to migrate to the tumor site, the influence of the protective tumor microenvironment, and the heterogeneity of surface antigens on tumor cells. Despite these results, CAR T cells have been proposed as a treatment approach for peritoneal carcinomatosis from colorectal and gastric origin. Local intraperitoneal administration of CAR T cells has been found to be superior to systemic administration, as this route is associated with increased tumor reduction, a more durable effect, protection against local relapse and distant metastases, and fewer systemic adverse effects. In this article we review the application of CAR T cells for the treatment of ovarian cancer and peritoneal carcinomatosis from ovarian cancer.